Social justice handbook : small steps for a better world - Cannon, Mae Elise, 1976- (Downers Grove, Ill. : IVP Books, 2009)
"Every day we are confronted by challenging societal problems, from poverty and institutional racism to AIDS and homelessness. It can all seem so overwhelming. But while none of us can do everything, all of us call do something. This handbook will help you discover what you can do." "Mae Elise Cannon provides a comprehensive resource for Christians committed to social justice. She presents biblical rationale for justice and explains a variety of Christian approaches to doing justice. Tracing the history of Christians in social engagement, she lifts out role models and examples from the Great Awakenings to the civil rights movement. A wide-ranging catalog of topics gives background information about justice issues at home and abroad." "The handbook includes dozens of practical exercises for taking action, highlighting how Christians and churches can make a difference. Also included are spiritual practices and resources to help us move from immobility to advocacy." "God has always worked through his people to accomplish improbable tasks. This handbook is an essential companion for living justly, loving mercy and walking humbly with your God."--BOOK JACKET.
Foundations of justice -- God's heart for justice -- Social justice : defining the issue -- A history of Christian social justice in the Americas -- Moving from apathy to advocacy -- Solutions to injustice -- Social justice issues -- Abortion -- AIDS -- AIDS : Africa -- AIDS : orphans -- AIDS : poverty -- AIDS : prevention -- AIDS : social impact -- AIDS : transmission -- AIDS : women -- Assisted reproductive technologies -- Bioethics -- Capital punishment -- Capitalism -- Children -- Child soldiers -- Class systems -- Cloning -- Consumerism -- Disaster relief -- Domestic abuse and violence -- Drugs and addiction -- Education : domestic -- Education : global -- Environmental justice -- Euthanasia and physician-assisted suicide -- Family -- Female genital mutilation -- Genocide -- Genocide : Darfur, Sudan -- Genocide : Rwanda -- Global economy -- Globalization -- Health care : domestic -- Health care : domestic children -- Health care : global -- Homelessness -- Housing -- Human rights -- Hunger -- Immigration -- Incarceration -- Malaria -- Microfinance -- Multiethnic churches and communities -- Physical disabilities -- Politics -- Poverty : Biblical perspectives -- Poverty : causes -- Poverty : cycles -- Poverty : domestic -- Poverty : global -- Poverty : statistics -- Prostitution -- Race : definition -- Race : incarceration -- Race : poverty -- Racial reconciliation -- Racism -- Racism : fear -- Racism : individual -- Racism : institutional -- Refugees -- Religious persecution -- Sex trafficking -- Sexism -- Sexuality -- Slavery -- Stem cell research -- Tuberculosis -- Urban decay -- Water -- White privilege -- Women -- Women : aging -- Women : body image -- Women : childbearing and family care -- Women : international leadership -- Women : poverty in the developing world -- Women : serving in the church -- Women : work and job opportunities -- Work : job training -- Work : living wage initiatives -- Work : the working poor.
Includes bibliographical references.
Keywords: Christian sociology; Church and social problems; Social justice -- Religious aspects -- Christianity; Christianity and justice